MAKAM-MAKAM KUNO DI TASIKMALA Latar Belakang Konsep dan Tokoh - Endang Widyastuti; Nanang Saptono (JURNAL PANALUNGTIK, 2019)
In the Tasikmalaya area many sites are found in the form of tombs and ancient grave complexes from the Islamic era. In archaeological studies, the tomb can be interpreted as a place where the body is buried and also the former location of the event by an important figure. The tomb can be interpreted as a grave and also petilasan. Through the tomb data can be revealed various aspects such as background concepts and figures buried. This study of ancient tombs in Tasikmalaya aims to reveal the background of the concept of site selection and the background of the buried figure. The research method is qualitative research through descriptive type. Disclosure of research problems is obtained through literature study and trace data reinforcement in the form of manuscripts. Ancient tombs in Tasikmalaya are on the plain and on top of a hill. The tomb at the top of the hill shows the continuity of previous cultural concepts, namely that high ground in the form of a hill or mountain is a sacred place. Some figures who are buried have a big role in the welfare of the community in the past, namely the opening of the Cibeureum situ.